Altered lower extremity muscle activity patterns due to Iliopsoas tightness during single-leg landing - Georgian Badicu (NATURE PORTFOLIOHEIDELBERGER PLATZ 3, BERLIN 14197, GERMANY, 2025)
This study aims to investigate the impact of iliopsoas (IL) tightness on lower extremity muscle activity during single-leg landing, focusing on how IL tightness influences joint protection through feed-forward and feed-back pathways that address known impaired neuromuscular mechanisms and provide a set of variables with which to assess and design the ongoing change from both prevention and management. A cross-sectional study of 28 male soccer players (ages 11–14 yrs) divided into IL tightness (n=14) and normal hip flexor length (n=14) groups assessed hip extension range using the modified Thomas test. Electromyography recorded muscle activity (gluteus maximus [GM], adductor magnus [AM], biceps femoris [BF], rectus femoris [RF], soleus [SOL], and multifidus [MF]) during single-leg landing, with RMS values computed over 50 ms epochs, collected 300 ms before and after ground contact, and normalized to maximal voluntary isometric contractions (MVIC). Statistical analysis using Kolmogorov-Smirnov and homoscedasticity tests confirmed normal distribution and homogeneity. Independent-sample t-tests compared muscle activity between groups and Cohen’s d effect size was calculated. All analyses were done using SPSS with significance set at p≤0.05. Specifically, participants with IL tightness had reduced activation of the RF (p=0.01) and SOL (p=0.003) during feed-forward action and increased activation of the MF compared to the normal group (p=0.008). During feed-back action, those with IL tightness demonstrated increased activation of the GM (p=0.01), BF (p=0.03), AM (p=0.01) and MF (p=0.017), whereas showing reduced activation of the RF (p=0.02) and SOL (p=0.01). Subtle differences were observed in how adolescent soccer players with iliopsoas tightness utilize their lower extremity muscles through kinetic chains during single-leg landing compared to healthy controls. These findings enhance our understanding of the complex functional consequences of iliopsoas tightness on motor control changes and underscore the importance of monitoring the effectiveness of interventions aimed at joint protection in this specific demographic.
-